Cybersecurity Awareness Tracker (CySAT) / Anas Rayyan Muhammad Shaifuddin ... [et al.] - Muhammad Shaifuddin, Anas Rayyan; Muhammad Shaifuddin, Amir Rayyan; Hasnan, Suhaily; Mohamed Hussain, Alfiatul Rohmah (2021)
Cybercrime is globally disruptive and economically harmful, causing billions of dollars in financial losses and negatively impacting individuals and organisations. It threatens national security and diminishes trust in the digital economy and the internet. In this COVID-19 pandemic era, most activities have shifted from offline to online mediums, increasing malware and ransomware attacks. Previously, bullying may have occurred on school grounds. Still, currently, it happens in the cyber world, which revolves around emotions to take revenge that negatively impacts the individual involved. Thus, the CyberSecutity Awareness Tracker (CySAT) is invented purposely to measure the level of cybersecurity awareness among individuals to build a strong communications channel for addressing cyber threats. Besides, CySAT also aims to prevent the occurrence of cybercrimes by utilising the critical elements of cybersecurity to promote the importance of fighting against cybercrimes. The CySAT is beneficial to society as it promotes cybersecurity awareness and serves as a cybersecurity prevention mechanism. The CySAT is uniquely innovated to assist individuals, specifically school students who are vulnerable to such crime, to measure the level of cybersecurity awareness.